Psychohygienic evaluation of depression level among Ukrainian youth forced to emigrate to Canada due to the war in Ukraine - Kozyr , Olena; Blagaia , Anna (The Ukrainian Scientific Medical Youth Journal, 2023)
the ongoing war in Ukraine since 2014 has led to the forced migration of thousands of people, resulting in a range of social and psychological problems, including depression. In light of this, the purpose of the research was to investigate the level of depression among youth who were forced to emigrate abroad due to the war. The study was conducted in Canada in 2023 using the Patient Health Questionnaire-9 of young people aged 16 to 30 years old who emigrated from Ukraine due to the war escalation on the 24th of February 2022. The PHQ-9 is a questionnaire used to assess the level of depression symptoms in the last two weeks based on 9 questions which show the level of the depression disorder or indicate the risks of its development. The research aims to raise awareness of the psychological well-being issue among war-displaced people between Russia and Ukraine to determine the level of depression, which allows providing practical recommendations for managing depression in the context of migration and developing psychological support and rehabilitation programs for this population. The study's findings suggest that a moderate level of depression, with increased levels of the moderate option, was observed among Ukrainian refugees aged 16 to 30 years old who migrated to Canada. The results also showed that the number of respondents who did not have signs of depression decreased due to the war. The average value of the sample slightly increased from 9.4 in 2022 to 10.9 in the current study. However, values of 9 and 10 are borderline for distinguishing "mild" and "moderate" levels of depression, so it can be assumed that this year was transitional between these conditions. The results of studying the most popular answers to some survey questions show that problems with falling asleep, poor sleep quality or too much concern more than half of the respondents almost every day. It can be argued that the stress associated with migration and war significantly affected the quality of sleep among young people. One-third of respondents reported poor appetite or overeating, which can be resolved with simple recommendations and advice. These findings highlight the potential need for mental health support for this population. The data obtained can be useful for government agencies in Canada and Ukraine, social services, psychological counsellors, and all those working with military and civilian refugees in the territories of North America and Europe.